2019
DOI: 10.1002/jimd.12007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic perturbations in classic galactosemia beyond the Leloir pathway: Insights from an untargeted metabolomic study

Abstract: Classic galactosemia (CG) is an autosomal recessive disorder that impacts close to 1/50000 live births in the United States, with varying prevalence in other countries. Following exposure to milk, which contains high levels of galactose, affected infants may experience rapid onset and progression of potentially lethal symptoms. With the benefit of early diagnosis, generally by newborn screening, and immediate and lifelong dietary restriction of galactose, the acute sequelae of disease can be prevented or resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(53 reference statements)
2
6
1
1
Order By: Relevance
“…The results of our metabolomics analysis revealed that CG does not only compromise the Leloir pathway, but also involves other metabolic pathways including the glycolytic pathway, the pentose phosphate pathway, and nucleotide metabolism. Our results confirm the finding of the only previous metabolomics study in CG that multiple pathways are affected 8 . The earlier metabolomics study reported perturbations in glutathione metabolism, amino acids and mitochondrial pathways, which were not replicated in our study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results of our metabolomics analysis revealed that CG does not only compromise the Leloir pathway, but also involves other metabolic pathways including the glycolytic pathway, the pentose phosphate pathway, and nucleotide metabolism. Our results confirm the finding of the only previous metabolomics study in CG that multiple pathways are affected 8 . The earlier metabolomics study reported perturbations in glutathione metabolism, amino acids and mitochondrial pathways, which were not replicated in our study.…”
Section: Discussionsupporting
confidence: 59%
“…Since galactose plays a central role in metabolism being involved in multiple different pathways, a full analysis of the metabolome may well shed new light on CG. Until now, the only published metabolomics study in CG patients evaluated plasma samples only 8 . It was demonstrated that not only the Leloir pathway is affected in CG, but that other metabolic pathways including amino acid metabolism and mitochondrial function are involved as well.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has emerged as a potentially useful diagnostic and prognostic tool that might explain disease pathogenesis ( Masood et al, 2021 ; Jacob et al, 2022 ; Jans et al, 2022 ). There currently needs to be more investigations on the pathophysiology of GAL that concentrate on urine or blood metabolomics profiling ( Taylor Fischer et al, 2019 ; Hermans et al, 2022 ). Therefore, investigating the GAL metabolomics profile may aid in finding potential biomarkers, shed light on the mechanisms behind the disease’s progression, and ultimately aid in its early detection.…”
Section: Introductionmentioning
confidence: 99%
“…As one of them, the determination of cortisol content in human scalp hair was recently used ( Ibrahim and Van Uum, 2014 ). Metabolomics studies provide novel tools in identifying biomarkers of diseases early diagnosis and treatment efficacy ( Taylor Fischer et al, 2019 ). Dooijeweert et al found that untargeted metabolomics in dried blood spots is a useful tool for pyruvate kinase deficiency diagnosis ( Van Dooijeweert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%